Pengaruh Net Profit Margin, Opini Audit, dan Ukuran Perusahaan terhadap Audit Delay pada Perusahaan Konstruksi yang Terdaftar di BEI 2019-2025 - Rifa Ranti Nuraini; Nur Zeina Maya Sari; Uswatun Hasanah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study examines the effects of Net Profit Margin, audit opinion, and firm size on audit delay among construction companies listed on the Indonesia Stock Exchange from 2019 to 2025. Audit delay is measured as the period between the fiscal year-end and the issuance date of the independent auditor’s report. Timely financial reporting is particularly important in the construction sector due to its complex long-term projects, progress-based revenue recognition, cost estimation, and high financial risks. Using a quantitative approach, the study analyzes secondary data from annual financial statements and independent auditor reports. The sample includes 14 construction companies observed over seven years, producing 98 observations. Panel data regression was conducted using EViews, with the Chow, Hausman, and Lagrange Multiplier tests identifying the Random Effect Model as the most appropriate estimation method. The findings show that Net Profit Margin does not significantly affect audit delay. In contrast, audit opinion and firm size have negative and significant effects, indicating that favorable audit opinions and larger company size are associated with shorter audit completion periods. Collectively, the three variables significantly influence audit delay, although they explain only 15.75% of its variation.